1977
DOI: 10.1002/art.1780200402
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes and complement catabolism in ankylosing spondylitis

Abstract: In serum samples from 37 patients with ankylosing spondylitis (AS), immune complexes were quantitated by the 125I-Clq binding test; in paired plasma samples the C3 breakdown product C3d was measured by an immunochemical method. Compared to results in 30 blood donors, the Clq binding activity was significantly (greater than 2 SD), although discretely, increased in 5 of 8 patients with seropositive AS, but not in other AS patients. All C3d levels were within the normal range. In a parallel investigation, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Then, it may be asked whether the uveitis which occurs in patients with diseases associated with immune complexes in serum, is not due to the intraocular deposition of these complexes. These diseases are, for example, ankylosing spondylitis (Gabay et al, 1977), sarcoidosis (Hedfors and Norberg, 1974), Behqet's syndrome (Williams and Lehner, 1977;Gupta et al, 1978;Gamble et al, 1979) and Crohn's disease (Doe et al, 1973;Jewell and MacLennan, 1973).…”
Section: The Pathogenic Mechanismsmentioning
confidence: 99%
“…Then, it may be asked whether the uveitis which occurs in patients with diseases associated with immune complexes in serum, is not due to the intraocular deposition of these complexes. These diseases are, for example, ankylosing spondylitis (Gabay et al, 1977), sarcoidosis (Hedfors and Norberg, 1974), Behqet's syndrome (Williams and Lehner, 1977;Gupta et al, 1978;Gamble et al, 1979) and Crohn's disease (Doe et al, 1973;Jewell and MacLennan, 1973).…”
Section: The Pathogenic Mechanismsmentioning
confidence: 99%
“…Most studies have shown an increase of C3 and C4 levels, while the evidence for activation of complement as studied by the presence of C3 or C4 conversion products is controversial. 6 We present the results of metabolic studies in AS patients and controls performed with purified radiolabelled C3. This factor has a central position in the complement system, as it is activated both by the classical and by the alternative pathways.7…”
mentioning
confidence: 99%
“…Recent reports [11][12][13] indicates that in seronegative spondyloarthritis, circulating immune complexes were pres ent, and that they can be correlated with the activity of the disease [II]. In our patient a large size (19S) circulating immune complex material was detected, and this size complex is known to produce experimentally, immune complex disease [14,15].…”
Section: Discussionmentioning
confidence: 94%